-6(t-2)-(t+8)=8

Simple and best practice solution for -6(t-2)-(t+8)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(t-2)-(t+8)=8 equation:



-6(t-2)-(t+8)=8
We move all terms to the left:
-6(t-2)-(t+8)-(8)=0
We multiply parentheses
-6t-(t+8)+12-8=0
We get rid of parentheses
-6t-t-8+12-8=0
We add all the numbers together, and all the variables
-7t-4=0
We move all terms containing t to the left, all other terms to the right
-7t=4
t=4/-7
t=-4/7

See similar equations:

| 18+6x=36x+48 | | 3x/10-3=12 | | 7x-5=3x-4+×+5 | | 9+5(x-1)=2-5(x-6) | | 12x-8x+2=12 | | -4=c/3 | | -7x-8=x-24 | | x+131=180 | | 12x-16=3x-4 | | 40x=50(x-1) | | 9+8x-9-5x+3 = 9+(8x-9)-5x+3 | | 2v-14=16 | | 2-b/3=2/5 | | 18-3xx=-2 | | -2-4r=44 | | -2x^2+260x-5000=0 | | 9+8x-9-5x+3 = 9+(8x-9)-5x+3 | | -2-4r=446 | | 3x+4x+3x=180,3x+4x=7x,7x+3x=10X,10X=180,180/10=18,X=18° | | 4x+1.5=3x−3+2 | | 4/5m-3=1/5m | | u÷3=6 | | y-13=×4 | | 6=2+7y | | 7/10b=6 | | x^2+10x=5000 | | 3+x-4+5-6=12 | | u-39=8 | | -6n-10=4 | | 0.6x-9=-6 | | c−2=3 | | 10+10x10=+10 |

Equations solver categories